2018
DOI: 10.1007/s00068-018-0920-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of quality of life after major trauma: a spanish follow-up cohort study

Abstract: The quality of life score improves during the first year after major trauma. However, it does not return to the reference levels for the normal population. Female gender and age ≥ 55 years are statistically significant determinants of poorer EQvas and EQus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…For example, the relationship between illness perceptions and quality of life has been studied in patients with irritable bowel syndrome (Knowles et al, 2017) and patients with injury (Lee et al, 2008). In previous studies, patients with injury were found to have relatively poor quality of life (Bayo et al, 2019;Van Son et al, 2017) and to have developed negative illness perceptions at 3 months after their injury (Lee et al, 2010). In another study of Taiwanese patients, three components of illness perception, including identity, consequences, and timeline, were identified as significant predictors of the physical quality of life of patients with injury at 3 months after injury (Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the relationship between illness perceptions and quality of life has been studied in patients with irritable bowel syndrome (Knowles et al, 2017) and patients with injury (Lee et al, 2008). In previous studies, patients with injury were found to have relatively poor quality of life (Bayo et al, 2019;Van Son et al, 2017) and to have developed negative illness perceptions at 3 months after their injury (Lee et al, 2010). In another study of Taiwanese patients, three components of illness perception, including identity, consequences, and timeline, were identified as significant predictors of the physical quality of life of patients with injury at 3 months after injury (Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The current study combined injury coding and inclusion on the basis of AIS08 with the EQ-5D-5L. Only one MT study [ 13 ] with AIS08 injury coding that reported QoL and had general inclusion criteria used the 5L version (median EQ-US ≈ 0.80, taken from graph). MT patients have higher mortality rates and more frequently need intensive care and urgent surgery when the ISS is derived from AIS08 compared to older AIS revisions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…AIS revisions better reflect contemporary state of the art of trauma care. A few QoL studies focusing on MT have used more recent AIS revisions for calculating ISS in their cohort [ 10 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horackova et al 2019 presented the prevalence of late-life depression ranging from 17 to 35% across European regions and reported a “gap in mental health service use” in those countries [ 35 ]. Llaquet Bayo et al 2019 analysed in their Spanish follow-up study parameters associated with a worse health-related quality of life assessed by the EQ-5D-5L™ in 200 major trauma patients [ 38 ]. They reported an age greater or equal 55, female gender and unskilled employment found to be risk factors for a lower EQ VAS; female gender was most importantly associated with pain and – consistent with our analysis with depression/anxiety.…”
Section: Discussionmentioning
confidence: 99%